Case report: Therapeutic drug monitoring and CYP2D6 phenoconversion in a protracted paroxetine intoxication - Damborská, Alena; Hanáková, Lenka; Pindurová, Eva; Horská, Kateřina (Frontiers in Pharmacology, 2024)
Objective: The cytochrome P450 2D6 (CYP2D6) is an enzyme involved in the oxidative biotransformation of various widely used drugs, including paroxetine, a substrate and strong inhibitor of the enzyme. The aim is to report on a case of protracted intoxication with paroxetine after a single overdose in a genotype-predicted intermediate CYP2D6 metabolizer. Observation: A 49-year-old man was receiving chronic treatment for more than six years with paroxetine 60 mg/day for an indication of agoraphobia. The patient ingested fifty 20 mg tablets of paroxetine in a suicide attempt. The toxic plasma level, accompanied by delirium, persisted for approximately one month after the overdose. According to the genotype profile, the patient was evaluated as an intermediate metabolizer with reduced CYP2D6 enzyme activity. Conclusion: As a consequence of the suicide attempt with overdose and the chronic paroxetine treatment that preceded it, phenoconversion to a poor metabolizer with very low CYP2D6 enzyme activity is suggested as contributing to an extremely long intoxication accompanied by delirium. Prolonged monitoring over a standard 24 hours of both physical symptoms and drug plasma levels, together with a genetic profile assessment and phenoconversion consideration, is recommended after a single overdose in patients chronically treated with paroxetine.